Mathematical models in nursing research - Teresa Rea; Assunta Guillari; Consolato Sergi; Nicola Serra (SAGE Publishing, 2020)
This paper discusses the use of advanced mathematical tools in nursing research, such as mathematical models used in medicine for description and prediction of experimental tumor growth. They are rarely used in nursing research, but fortunately in the last decade, their use is increased, particularly due to the artificial intelligence and Big Data, with great benefits for further development of nursing. Therefore, a strong interaction between nurses and mathematicians is needed to improve nursing research, and consequently the nurses performance in daily work.